Unexpected effects of land fragmentation - Hoang Trung Xuan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Using instrumental variable method and Viet Nam Access to Resources Household Surveys of 2008-16, I examine the effect of land fragmentation on child outcomes. The study shows that higher land fragmentation decreases child school dropout. Land fragmentation has significant impacts on school dropout of children aged 10-15, however, it does not have any impact on school dropout of children aged 6-10. I explain these findings through one particular mechanism - that is women empowerment. A higher level of land fragmentation increases women's empowerment to decide on visits to family, friends or relatives, on the purchase of daily goods, on large purchases, on her own health, and on her children's health.
Keywords: O12; Q12; A20; C26; 330; instrumental variable; land fragmentation; Viet Nam